The Effect of Canva for Education on Learning Outcomes in Islamic Education Subjects: Learning from the Services of Caliphs Uthman bin Affan and Ali bin Abi Talib (Journal of Didactic Studies, 2024)
Islamic religious education has several classic problems, such as learning materials that are considered uninteresting, teaching methods that are unpleasant and tend to be boring and do not motivate students. Technological intervention in Islamic religious education can play an important role in helping the learning process so that learning objectives can be achieved as expected. The purpose of this study was to determine the effect of Canva media on student learning outcomes in Islamic religious education. The research method used was pre-experimental with a one-group pretest-posttest design with descriptive and inferential statistical analysis techniques to analyze sample data, the results of which were applied to the population. The results showed that the use of Canva for Education media had a significant and positive effect on student learning outcomes in Islamic Religious Education (PAI) for sixth grade students at SDN Bingawati. The pre-test scores (averaging between 20.8 and 53.91) led to much higher post-test scores (averaging between 70.31 and 89.68). This study reinforces the statement that information presented in both text and visual forms is easier for the brain to process.